Análisis paramétrico para la evaluación de operación de las unidades de generación de la Central Hidroeléctrica Illuchi N° 2” - León Reinoso, Edwin Nicolás (2021)
The research project seeks to obtain the maximum efficiency of the Illuchi N ° 2 hydroelectric plant of the Empresa Eléctrica Provincial Cotopaxi SA, through the parametric analysis of the operational variables and that has been validated through field measurements with the experimental method, a Once the process was characterized, the best operating conditions focused on reducing electrical and mechanical losses were determined. During the analysis, the variables with the greatest impact that reflect deficiencies in the process were identified. To make the mathematical solution process more accurate and reliable, the Engineering Equation Solver (EES) was used, mainly taking advantage of the module of mathematical, fluid and thermophysical functions to efficiently solve hundreds of equations, therefore that, a model code was developed to carry out the identification, evaluation and characterization. The parametric model considered running a family of probabilities with a finite number of parameters looking for the best option or operating condition for the maximization of electrical energy production, with the application of these it was possible to avoid losses by 4.4% strictly due to the control of the factors analyzed, which is equivalent to 1145.65 MW / h and USD. 43,533.03 per year, seeking as a result the application of a proposal and recommendations based on the analysis with operational provisions and slogans only without investing money since the object of study sought to avoid controlling losses in the operation of the plant to improve availability , efficiency, performance and with it the profitability of the plant.